Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di CV Maju Djaya Beton Singosari - Tria Khotami Ayuba; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of work stress and work environment on employee performance at CV Maju Djaya Beton, Singosari. The data collection method in this study used a questionnaire with a total sample of 42 employees. The data analysis method used in this study is Multiple Linear Regression Analysis. Based on the results of this study that work stress and work environment have no effect on employee performance at CV Maju Djaya Beton, Singosari. However, when tested simultaneously work stress and work environment affect employee performance. Keywords: Work Stress, Work Environment, and Employee Performance